5,6-Dihydrothymine impairs the base excision repair pathway of a closely opposed AP site or single-strand break. - Byrne, S; Cunniffe, S; O'Neill, P; Lomax, M (2009)
Ionizing radiation can induce clustered DNA damage (two or more lesions formed within one to two helical turns of DNA by passage of a single ionization track). Using oligonucleotide constructs containing clustered DNA lesions at defined positions, evidence is presented demonstrating that a persistent 5,6-dihydrothymine (DHT) lesion reduces the efficiency of rejoining, in mammalian nuclear extracts, of an opposing AP site or SSB when within 5 bp. The efficiency of repair of the SSB is reduced when DHT is present on the opposing strand in both the 3' and 5' orientation; however, the efficiency of the repair of the AP site is reduced only when DHT is present 3' to the AP site. DNA polymerase beta and ligation are particularly impaired by DHT. It was also shown that in the presence of DHT there is a greater dependence on the long-patch base excision repair pathway than when DHT is absent. In addition, immunodepletion of XRCC1 from the nuclear extracts slows down the initial rate of repair of the AP site in both the presence and absence of DHT, but immunodepletion of XRCC1 has no influence on the repair of an SSB.